Modernity and its agencies : young movements in the history of the South - Atabaki, Touraj; SEPHIS (Programme : Netherlands) (New Delhi : Manohar Publishers & Distributors, 2010)
Contributed papers presented at a workshop held at Uzbekistan Academy of Sciences in Tashkent in 2003 organized by SEPHIS.
"SEPHIS."
Includes bibliographical references and index.
Keywords: Youth movements -- Asia -- History -- Congresses; Youth movements -- Africa -- History -- Congresses